Novel of (polymer blend-Fe3O4) magnetic nanocomposites: preparation and characterization for thermal energy storage and release, gamma ray shielding, antibacterial activity and humidity sensors applications - Hashim, Ahmed; Agool, Ibrahim R.; Kadhim, Kadhim J. (Journal of materials science. Materials in electronics, 2018)
Preparation of (PVA-PEG-PVP-Fe 3 O 4 ) magnetic nanocomposites and studying their structural, electrical and optical properties have been investigated. The results showed that the D.C., A.C. electrical and optical properties of (PVA-PEG-PVP) blend are improved with increase in Fe 3 O 4 nanoparticles concentration. The (PVA-PEG-PVP-Fe 3 O 4 ) nanocomposites tested for thermal energy storage and release, gamma ray shielding, antibacterial activity and humidity sensors applications with high quality, lightweight and good elastic. The results of showed that the melting and solidification time for thermal energy storage and release decrease with adding Fe 3 O 4 nanoparticles concentrations. The attenuation coefficients of gamma radiation increase with increase in nanoparticles concentration. The inhibition zone for antibacterial application increases with increase in Fe 3 O 4 nanoparticles concentration. The nanocomposites have highly sensitivity for humidity.